2017
DOI: 10.3923/ijps.2017.403.414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct-fed Microbials on Intestinal Villus Height in Broiler Chickens: A Systematic Review and Meta-Analysis of Controlled Trials

Abstract: Records identif ied through database searching (PubMed and scopus) (n = 15, 987) Duplicates removed by title, author and journal (n = 5,520) Records after duplicates removed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Ştef et al [47] have also demonstrated the positive effect of probiotics on the growth performances, gut health and disease prevention. Heak et al [20] have demonstrated that there have not been a significant positive effects of probiotics on the crypt depths bot in cecum and ileum (n=96 comparisons in research studies). We determined in this study that probiotics were more effective on the villus heights and crypt depths both in the ceca and ileum of chickens both infected and not.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Ştef et al [47] have also demonstrated the positive effect of probiotics on the growth performances, gut health and disease prevention. Heak et al [20] have demonstrated that there have not been a significant positive effects of probiotics on the crypt depths bot in cecum and ileum (n=96 comparisons in research studies). We determined in this study that probiotics were more effective on the villus heights and crypt depths both in the ceca and ileum of chickens both infected and not.…”
Section: Discussionmentioning
confidence: 98%
“…The disease causes to death or sub-latent chronic disease. Even though chicken is not died, the chronic form and sub-clinic form of the disease may cause poor LBW, high FCR and secondary diseases [20,36] . In this study, the visible signs of coccidiosis infection in the ceca of chickens at 6 th day of post-infection has clearly demonstrated (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in the structure of the mucous membrane also take place when birds feed during intensely or experience hunger (Incharoen et al, 2010), are subject to manipulations (Yamauchi et al, 2010) involving addition of medical preparations of feed additives to their diet (Wijtten et al, 2012;Tsirtsikos et al, 2012;Incharoen, 2013;Cheled-Shoval et al, 2014) and stress situations (Varasteh et al, 2015;Marchini et al, 2016). At the same time, excessive impacts on the intestinal wall can cause pathological processes instead of adaptive reactions (Heak et al, 2017;Wang et al, 2018). A significant parameter for determining the efficiency of the digestive organs is the age formation of the nervous system (Goldstein & Nagy, 2008;Heanue et al, 2016;Chevalier et al, 2017).…”
Section: Introductionmentioning
confidence: 99%